Study of outcomes of delay in referral of patients with acute myocardial infarction - Jafar Shahbazpour; Mohammad Abbasi; Narges Eskandari; Mohammad Aghaali; Reza Norouzadeh (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Delay in seeking medical help in patients with acute myocardial infarction (AMI) challenges the patients in terms of diagnosis and treatment. This study aimed to evaluate the outcomes of delay referral (≥12 h) in patients with AMI. MATERIALS AND METHODS: In this retrospective cohort study, the medical records of 252 patients with AMI (2017-2019) admitted to Shahid Beheshti Hospital, Qom, Iran, was reviewed. Data collection tool was a researcher-made data sheet that included demographic characteristics, times, hospitalization costs, risk factors, history of heart disease, results of paraclinical tests, clinical information at the time of admission, and outcomes of delayed referral. Data were analyzed using t-test, Chi-square, Kaplan-Meier estimator, log-rank test, Cox regression by STATA, and SPSS (version 25). RESULTS: The levels of troponin, creatine phosphokinase, lactate dehydrogenase were significantly higher in the delayed referral group (P < 0.05). After treatment, the cardiac ejection fraction was significantly different in the nondelayed referral (41.56 ± 9.16) and the delayed referral group (38.39 ± 11.01) (P < 0.001). There was no significant difference in the percentage of hospital deaths in the groups (P = 0.078). CONCLUSION: Delayed referral of patients with AMI is associated with decreased physiological cardiac function, which complicates recovery for these patients.